Interstitial cystitis associated with primary Sjögren's syndrome successfully treated with a combination of tacrolimus and corticosteroid: A case report and literature review. Issue 3 (3rd May 2016) - Ueda, Yo; Tomoe, Hikaru; Takahashi, Hiroyuki; Takahashi, Yuko; Yamashita, Hiroyuki; Kaneko, Hiroshi; Kano, Toshikazu; Mimori, Akio
Abstract : We report a case of interstitial cystitis (IC) associated with primary Sjögren's syndrome (SS) successfully controlled with combination therapy of tacrolimus and a corticosteroid. In 2011, a 69-year-old female, who had been diagnosed with primary SS 23 years ago, developed IC and was successfully treated with tacrolimus and prednisolone combination therapy. The mechanism of IC, including the involved autoimmunity, has not been elucidated. Clinical observation studies suggest a potential association between SS and IC. However, IC is currently thought to be underdiagnosed in patients with SS as well as in the general population. Based on our case and others reported previously, IC associated with SS responds well to immunosuppressive therapy. In particular, a combination of a calcineurin inhibitor (tacrolimus or cyclosporine) with a corticosteroid seems to be highly effective. The possibility of IC in patients with SS complaining of lower urinary tract symptoms without features of infection or other identifiable causes should be given attention.